Upregulation of retinal VEGF and connexin 43 in murine nonarteritic anterior ischemic optic neuropathy induced with 577 nm laser. (December 2022) - Rangel, Barbara; Mesentier-Louro, Louise A.; Lowe, Lauryn L.; Shariati, Ali Mohammad; Dalal, Roopa; Imventarza, Joel A.; Liao, Yaping Joyce
Abstract: Nonarteritic anterior ischemic optic neuropathy (NAION) is a common acute optic neuropathy and cause of irreversible vision loss in those older than 50 years of age. There is currently no effective treatment for NAION and the biological mechanisms leading to neuronal loss are not fully understood. Promising novel targets include glial cells activation and intercellular communication mediated by molecules such as gap junction protein Connexin 43 (Cx43), which modulate neuronal fate in central nervous system disorders. In this study, we investigated retinal glial changes and neuronal loss following a novel NAION animal model using a 577 nm yellow laser. We induced unilateral photochemical thrombosis using rose bengal at the optic nerve head vasculature in adult C57BL/6 mice using a 577 nm laser and performed morphometric analysis of the retinal structure using serial in vivo optical coherence tomography (OCT) and histology for glial and neuronal markers. One day after experimental NAION, in acute phase, OCT imaging revealed peripapillary thickening of the retinal ganglion cell complex (GCC, baseline: 79.5 ± 1.0 μm, n = 8; NAION: 93.0 ± 2.5 μm, n = 8, P < 0.01) and total retina (baseline: 202.9 ± 2.4 μm, n = 8; NAION: 228.1 ± 6.8 μm, n = 8, P < 0.01). Twenty-one days after ischemia, at a chronic phase, there was significant GCC thinning (baseline 78.3 ± 2.1 μm, n = 6; NAION: 72.2 ± 1.9 μm, n = 5, P < 0.05), mimicking human disease. Examination of molecular changes in the retina one day after ischemia revealed that NAION induced a significant increase in retinal VEGF levels (control: 2319 ± 195, n = 5; NAION: 4549 ± 683 gray mean value, n = 5, P < 0.05), which highly correlated with retinal thickness (r = 0.89, P < 0.05). NAION also led to significant increase in mRNA level for Cx43 (Gj1a) at day 1 (control: 1.291 ± 0.38; NAION: 3.360 ± 0.58 puncta/mm 2, n = 5, P < 0.05), but not of glial fibrillary acidic protein (Gfap) at the same time (control: 2, 800 ± 0.59; NAION: 4, 690 ± 0.90 puncta/mm 2 n = 5, P = 0.19). Retinal ganglion cell loss at day 21 was confirmed by a 30% decrease in Brn3a + cells (control: 2, 844 ± 235; NAION: 2, 001 ± 264 cells/mm 2, n = 4, P < 0.05). We described a novel protocol of NAION induction by photochemical thrombosis using a 577 nm laser, leading to retinal edema and VEGF increase at day 1 and RGCs loss at day 21 after injury, consistent with the pathophysiology of human NAION. Early changes in glial cells intercommunication revealed by increased Cx43+ gap junctions are consistent with a retinal glial role in mediating cell-to-cell signaling after an ischemic insult. Our study demonstrates an early glial response in a novel NAION animal model and reveals glial intercommunication molecules such as Cx43 as a promising therapeutic target in acute NAION. Highlights: Novel protocol of NAION leads to acute retinal edema and chronic RGCs loss, consistent with the pathophysiology of rodent and human NAION. Murine NAION induces significant increase in retinal VEGF levels, correlating with retinal thickening after insult. Early glial increase in connexin43 expression, reveals glial gap junctions as a promising therapeutic target in acute NAION.